To determine the age of Key, we can set up an equation based on the information provided. Let's denote the age of the oldest sibling as \( x \).
Since the siblings are born 2 years apart, we can define their ages as follows:
- Oldest sibling: \( x \)
- 2nd oldest: \( x - 2 \)
- 3rd sibling: \( x - 4 \)
- 4th sibling: \( x - 6 \)
- Youngest sibling (Key): \( x - 8 \)
Now, we can sum up their ages: \[ x + (x - 2) + (x - 4) + (x - 6) + (x - 8) = 70 \]
This simplifies to: \[ 5x - 20 = 70 \]
To find the equation in terms of Key's age \( a \), we know Key's age is \( a = x - 8 \).
From \( 5x - 20 = 70 \), we can isolate \( x \): \[ 5x = 90 \quad \Rightarrow \quad x = 18 \]
Now substituting \( x = 18 \) back to find Key's age: \[ a = x - 8 = 18 - 8 = 10 \]
However, to express this in terms of an equation to find \( a \), we can substitute \( a = x - 8 \) back into the equation derived from the sum of the ages: \[ 5(x - 8) + 20 = 70. \]
So, finally the equivalent equation using \( a \) becomes: \[ 5a + 20 = 70. \]
Thus, the correct equation to determine the age, \( a \), of Key is: \[ \boxed{5a + 20 = 70}. \]